THE THEORY AND PRACTICE OF OPERETTA ROLES - JORDÁN, Éva-Elena (Studia Universitatis Babes-Bolyai Musica, 2019)
The journey of operetta performers in creating their role, from the initial preparations to the premiere. The personal, organizational, artistic and professional aspects of the preparation process: studying the score, individual practice, professional auditions, the casting process, individual rehearsal time with piano accompaniment, learning the stage direction, the staging of dramatic moments, collaborating with the orchestra, vocal synchronization with the stage partners, preservation of vocal accuracy and abilities, in all stage situations, creating and learning the stage movement and situations required, the importance of accurate diction while singing and uttering dialogues, singing and acting in costume, familiarizing one’s self with the set, the rhythm of the scenes, stage orientation, establishing the rhythm of the stage portrayal, establishing a relationship with the audience, paying attention to their reactions, stage presence throughout the performance, the ability to improvise in unforeseen situations, appropriate reactions, gestures and behavior during applause. We will thus analyze a few primadonna and grande dame roles from the standpoint of the above-mentioned elements.